2017
DOI: 10.1159/000472253
|View full text |Cite|
|
Sign up to set email alerts
|

Dermoscopy of Malignant Skin Tumours: What's New?

Abstract: Dermoscopy represents a new and effective tool that assists dermatologists in improving the accuracy of clinical diagnosis in onco-dermatology. The aim of this article is to provide an overview of the latest and important dermoscopic progress and observations in this ever-evolving field of dermatology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 38 publications
4
19
0
3
Order By: Relevance
“…Amelanotic and hypopigmented skin lesions represent one of the most challenging clinical scenarios for dermatologists because many benign and malignant tumours, as well as inflammatory or infectious diseases, may look similar at clinical and dermoscopic examination. About 2% of melanomas may present as pink lesions, and this peculiar clinical presentation is often responsible for delayed diagnosis and poorer overall survival as compared to pigmented melanoma . Moreover, some of the most aggressive primary skin tumours, such as Merkel cell carcinoma, as well as cutaneous metastasis, are commonly characterized by a pink appearance.…”
Section: Introductionmentioning
confidence: 99%
“…Amelanotic and hypopigmented skin lesions represent one of the most challenging clinical scenarios for dermatologists because many benign and malignant tumours, as well as inflammatory or infectious diseases, may look similar at clinical and dermoscopic examination. About 2% of melanomas may present as pink lesions, and this peculiar clinical presentation is often responsible for delayed diagnosis and poorer overall survival as compared to pigmented melanoma . Moreover, some of the most aggressive primary skin tumours, such as Merkel cell carcinoma, as well as cutaneous metastasis, are commonly characterized by a pink appearance.…”
Section: Introductionmentioning
confidence: 99%
“…As a routine procedure in our center, a clinical and dermoscopic diagnosis of BCC is usually adequate to warrant a direct treatment, while the pretreatment confirmation of the diagnosis with a partial biopsy is only optional for the attending clinician. This is mainly associated with the introduction and widespread use of dermoscopy, which is known to significantly improve the clinical recognition of BCC 12‐15 . Indeed, our results revealed that in 77.5% of tumors the final treatment was applied based only on clinical and dermoscopic diagnosis.…”
Section: Discussionmentioning
confidence: 84%
“…A red nodule mimicking a benign tumor could be due to AM, whose dermatoscopy usually shows negative network, white shiny structures, milky red areas, polymorphous vessels, and residual areas of pigmentation [9][10][11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%